Competitive type of the criminal procedure - Моторигіна, М. Г. (Theory and practice of jurisprudence, 2016)
This article deals with the main elements of competitiveness, defines essence of its practical significance, analyses the CPC of Ukraine novelties, connected with competitiveness, in particular, the definition of the party in criminal proceedings in the national legislation is researched, its comparison with definitions, fixed in the criminal procedure codes of the other countries is made.